2015
DOI: 10.1039/c5cp05679a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial band alignment for photocatalytic charge separation in TiO2nanotube arrays coated with CuPt nanoparticles

Abstract: n-Type anatase-phase one-dimensional TiO2 nanostructure arrays coated with nanoparticles of Cu or CuPt have emerged as high performance photocatalysts for both photooxidation and photoreduction. The properties of the catalyst-promoter interface are recognized to be critical to this high performance but are largely unknown. Using X-ray and ultraviolet photoelectron spectroscopies (XPS/UPS), we probed the electronic properties of the CuPt-TiO2 interface in transparent TiO2 nanotube arrays (TTNTAs) coated with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 77 publications
(85 reference statements)
5
58
0
Order By: Relevance
“…Preliminary characterization of the ZnO/TiO 2 heterostructures was done here by deriving the position of the valence band maxima ( Figure 5 ). The valence band maximum (VBM) of the bare TiO 2 layer is located at 3.25 eV below the Fermi level, in agreement with the literature [ 47 ], while the VBM of the heterostructure is located at 2.3 eV below the Fermi level, irrespective of the ZnO coverage. Therefore, only one VB-XPS spectrum for the loaded samples was introduced ( Figure 5 b).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Preliminary characterization of the ZnO/TiO 2 heterostructures was done here by deriving the position of the valence band maxima ( Figure 5 ). The valence band maximum (VBM) of the bare TiO 2 layer is located at 3.25 eV below the Fermi level, in agreement with the literature [ 47 ], while the VBM of the heterostructure is located at 2.3 eV below the Fermi level, irrespective of the ZnO coverage. Therefore, only one VB-XPS spectrum for the loaded samples was introduced ( Figure 5 b).…”
Section: Resultssupporting
confidence: 88%
“…Apart from the elemental and chemical information on core-level photoelectron lines, the XPS technique allows additional investigation of band gap and valence band localization and structure, despite not being as complete as the ultraviolet photoelectron spectroscopy (UPS) [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…S1a † ), a photodeposition method (Fig. S7 † ) was adopted 29 under the protection of a N 2 atmosphere in methanolic solvent, using platinum acetylacetonate and copper acetylacetonate as precursors. Energy dispersive spectroscopy (EDS) mapping ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These nanoparticles were further identified by HRTEM (Figure 1 e), in which the d spacing of lattice fringes could be attributed to Pt (111, 0.226 nm) and anatase TiO 2 (101, 0.350 nm). [27] The copper species were not observed at this resolution, suggesting the existence of smaller clusters. Energy-dispersive X-ray (EDX) mapping showed that Cu and Pt were dispersed homogeneously (Figure 1 f), in good agreement with the XRD results.…”
Section: Angewandte Chemiementioning
confidence: 89%